Teachers' Professional Competence in Integrating Catholic Values at Elementary School - Sagita; Paulina Maria Ekasari Wahyuningrum; Emilianus Sember Sawo (Kirana Publisher (KNPub), 2026)
This study aims to describe the professional competence of Catholic Religious Education (CRE) teachers in integrating Catholic’s values explicitly and in a structured manner into learning at Santo Don Bosco Catholic Elementary School, Palangka Raya. The study employed a qualitative descriptive approach. The primary data sources were three CRE teachers, reinforced by a learning experience questionnaire administered to 18 students. Data were collected through in-depth interviews, documentation, and questionnaires, then analyzed through data reduction, data display, and conclusion drawing, with validity ensured through triangulation. The results show that the professional competence of CRE teachers in integrating Catholic’s values is good and developing, reflected in the dimensions of planning, implementation, and evaluation. Value integration is carried out through three domains, namely moral knowing, moral feeling, and moral action. The questionnaire results indicate that 66.7% of students stated that Catholic’s values were always explained in an easily understandable way, and 66.7% stated they were always given tasks to do good to others. The teachers' main challenges are being consistent role models, dealing with the diversity of student characteristics, and forming faith habits in lower-grade children, which require repeated and patient processes.